Economic policy uncertainty and firm innovation: Evidence from a risk-taking perspective - Lou, Zhukun; Chen, Siyu; Yin, Wenwei; Zhang, Chuan; Yu, Xiaoyu (International review of economics & finance, 2022)
This study investigates the impact of economic policy uncertainty (EPU) on firm innovation. Using data on China's A-share listed companies for 2001–2017, we find that EPU is in general negatively associated with firms' innovation output. Further, we observe that the negative association between EPU and innovation mainly exists in firms whose executives have a low risk preference and in firms with weak risk-taking ability. Additionally, we find that corporate innovation has a stronger positive effect on firm value when EPU is lower. Our research provides important evidence about the effect of EPU on firm innovation from a risk-taking perspective.